Influence of drying conditions on ascorbic acid during convective drying of whole persimmons - Nicoleti, Joel F.; Silveira, Vivaldo; Telis-Romero, Javier; Telis, Vania R. N. (Taylor & Francis Inc, 2007)
Degradation kinetics of food constituents may be related to the matrix molecular mobility by glass transition temperature. Our objective was to test this approach to describe ascorbic acid degradation during drying of persimmons in an automatically controlled tray dryer with temperatures (40 to 70 degrees C) and air velocities (0.8 to 2.0 m/s) varying according a second order central composite design. The Williams-Landel-Ferry model was satisfactorily adjusted to degradation curves for both control strategies adopted-constant air temperature and temperature fixed inside the fruit. Degradation rates were higher at higher drying temperatures, independent of the necessary time to attain the desired moisture content.
Keywords: glass transition; kinetics; thermal degradation; vitamin C; WLF model